2006
DOI: 10.1002/pssb.200672538
|View full text |Cite
|
Sign up to set email alerts
|

Impurity‐related optical properties in rectangular‐transverse section GaAs–Ga1–xAlxAs quantum well wires: Hydrostatic pressure and electric field effects

Abstract: Using a variational procedure within the effective mass approximation, we have calculated the influence of an applied electric field and hydrostatic pressure on the shallow-impurity-related optical properties in a rectangular-transverse section GaAs -Ga 1-x Al x As quantum well wire. The electric field is applied in the plane of the transverse section of the wire and different angular directions have been considered. The results presented are for the impurity binding energy, its corresponding density of impuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The studies have shown a good agreement with experimental results for the pressure coefficient of the photoluminescence peak transitions. The works of González et al 27 and Kasapoglu et al 9, 28 associated with impurities in QW and QWW have shown that the binding energy increases linearly with hydrostatic pressure in the direct gap regime and for pressures above the crossing between the Γ and X conduction band minima – for the barrier material –, the binding energy grows to a maximum and then decreases. The latter behavior is due to the lowering of the effective potential that confines the carriers in the region of the QW, QWW, or QD.…”
Section: Introductionmentioning
confidence: 99%
“…The studies have shown a good agreement with experimental results for the pressure coefficient of the photoluminescence peak transitions. The works of González et al 27 and Kasapoglu et al 9, 28 associated with impurities in QW and QWW have shown that the binding energy increases linearly with hydrostatic pressure in the direct gap regime and for pressures above the crossing between the Γ and X conduction band minima – for the barrier material –, the binding energy grows to a maximum and then decreases. The latter behavior is due to the lowering of the effective potential that confines the carriers in the region of the QW, QWW, or QD.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental and theoretical investigations have been reported concerning the effects of hydrostatic pressure and compressive stress on shallow-donor impurity states in GaAs/Al x Ga 1−x As quantum wells (QWs) and quantum-well wires (QWWs). Gonzalez et al [7] studied the optical properties related to pressure in QWWs, and Odhiambo [8] reported a comparative study of hydrostatic pressure in single quantum wells (SQWs) and double quantum wells (DQWs). The -X crossover [9,10] was observed experimentally by Venkateswaran et al, who studied the pressure dependence of photoluminescence spectra in multiple quantumwell (MQW) structures.…”
Section: Introductionmentioning
confidence: 99%